Toward Impacting Medical and Psychiatric Comorbidities in Persons with Intellectual/Developmental Disabilities: An Initial Prospective Analysis - Gentile, Julie P. (Innov Clin Neurosci, 2014)
Objective: The purpose of this study was to determine the effectiveness of psychiatric medical services, counseling, and behavioral treatments for adult patients with intellectual disabilities plus behavioral disorders and/or emotional distress. Methods: Behavioral and medical data were collected at six and 12 months for a consecutive series of 141 adult patients with mild, moderate, or severe/profound intellectual disabilities who had been referred to a dual diagnosis mental health clinic, and treatment outcomes were compared. Results: Most improvement in behavioral problem severity occurred at six months, then plateaued. Treatment improvement for subjects with anxiety disorders was statistically significant across all interventions. In this sample, as expected, patients with intellectual disability had higher incidences of medical illnesses than the general population. Conclusions: Subjects with more behavioral (overt) symptoms tended to receive referrals for behavioral support, and subjects with less overt symptoms were referred to counseling. In a follow-up study, similar individuals with moderate intellectual disabilities will be seen psychiatrically, but then randomly assigned to either supportive counseling or behavior support, or both. They will be followed prospectively, to determine the relative benefits of supportive psychotherapy, behavior support, or a combination, and for what duration of time the treatment should be continued.